Applying IROC Method in Patent Submission Evaluation in Indonesia: A Comparison with MAGIQ and AHP - Ambarsari, Erlin Windia; Rahman, Vierhan; Cholifah, Wahyu Nur (PDSI, 2023)
This study applies the Improved Rank Order Centroid (IROC) to the Indonesian patent submission process within a Multi-Criteria Decision Making (MCDM) framework. The study evaluates four primary elements in patent assessment: